Impact of Fiscal and Monetary Policies Complementary to the Economic Growth of Lao PDR - CHANMAVONG , Aksonexay; CHANTHAVONE, Thongphanh; PHOUNNALY, Phaivanh; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
Lao PDR is one of the least developed countries, our aim is to improve the economy to bring people out of poverty. The government plays a significant role in Lao economic development by setting fiscal policy and monetary policy through expenditure, customs-taxation, money supply, exchange rate and interest rate. Since 1997, the Lao PDR has been affected by the Asian financial crisis. Lao PDR was under severe inflationary pressure at that time, in 1998 and 1999 there were inflation rates of 142.0% and 108.3% respectively. So, the government applied the fiscal and monetary policies in order to improve the economic system. The study of the impact of fiscal and monetary policies on the economic growth of the Lao PDR provided quantitative analysis by using secondary data annually from 1990-2018 and by testing the short-term impact and long-term impact of fiscal and monetary policies' impact on future economic growth in Lao PDR. The researchers wanted to study how fiscal and monetary policies are affecting the Lao economy and guide the government to adapt to the changing economic situation. The result of the study found that the long-term impact of fiscal and monetary policies was complementary to the economic growth of Lao PDR through government expenditure, customs- taxation, determination of money supply in the economic system and exchange rate. Fiscal and monetary policies through taxation and exchange rate could also have an impact on the economic growth of the Lao PDR in the short term and the deviation to the long-term equilibrium point is at a speed of 24.86%. When forecasting GDP growth in 2019-2020 by ARIMA models it showed that ARMA (1,2) is leading to a decrease in the rate of GDP growth of Lao PDR. So, the government should apply fiscal and monetary policies in line with the economic conditions, by using fiscal policy through government expenditure, customs-taxation as a stimulus for the private investment sector and consumption. Also, monetary policy through exchange rate to promote foreign direct investment (FDI).